2016
DOI: 10.14814/phy2.12663
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor REV-ERBαrepresses the transcription ofgrowth/differentiation factor 10and15genes in rat endometrium stromal cells

Abstract: Cellular oscillators in the uterus play critical roles in the gestation processes of mammals through entraining of the clock proteins to numerous downstream genes, including growth/differentiation factor (Gdf)10 and Gdf15. The expression of Gdf10 and Gdf15 is significantly increased in the uterus during decidualization, but the mechanism underlying the regulation of Gdf gene expression in the uterus is poorly understood. Here, we focused on the function of the cellular oscillators in the expression of Gdf fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…Compound 21 also caused significant increases in the expression levels of growth/differentiation factor Growth and differentiation factor 10 (GDF10) and Growth and differentiation factor 15 (GDF15) in uterine endometrial stromal cells (UESCs). These results show that cellular oscillators may serve an important role of regulating the expression of downstream genes during the differentiation of UESCs 89 .…”
Section: Overview Of Modulators Targeting Circadian Rhythmsmentioning
confidence: 71%
“…Compound 21 also caused significant increases in the expression levels of growth/differentiation factor Growth and differentiation factor 10 (GDF10) and Growth and differentiation factor 15 (GDF15) in uterine endometrial stromal cells (UESCs). These results show that cellular oscillators may serve an important role of regulating the expression of downstream genes during the differentiation of UESCs 89 .…”
Section: Overview Of Modulators Targeting Circadian Rhythmsmentioning
confidence: 71%
“…Another E2-specific and pregnancy-specific DEG, also related in tissue remodeling, is macrophage inhibitory cytokine-1 (MIC-1), also named growth differentiation factor 15 (GDF15), a member of the transforming growth factor-β (TGFB) superfamily, known to be expressed at high levels in human placenta [69]. GDF15 has been reported to be involved in actin cytoskeleton reorganization and remodeling [70] and is necessary for the maintenance of pregnancy in humans [71] and rats [72]. Intriguingly, it has been suggested that GDF15 participates in placenta development via promoting trophoblast cell invasion [73].…”
Section: Involvement Of Estrogen Signaling In Processes Related To Cementioning
confidence: 99%
“…Working on night or rotating shifts is linked to a greatly increased risk for women to develop breast and ovarian cancer, and for men to develop prostate cancer ( 69 71 ). Clock genes contribute to the occurrence and development of tumors by regulating and interfering with oncogenes (c-myc), tumor-suppressor genes (P53 and P21), genes involved in the regulation of the cell cycle (cyclins A, B1 and D1, and WEE1 G2 checkpoint kinase) and vascular endothelial growth factor, as well as affecting the internal secretion pathway ( 72 81 ) ( Fig. 1 ).…”
Section: Discussionmentioning
confidence: 99%